Computational Simulation of Microflaw Detection in Carbon-Fiber-Reinforced Polymers - Santos, Mário; Santos, Jaime; Petrella, Lorena (Electronics (Basel), 2022)
The evaluation of microflaws in carbon-fiber-reinforced composite laminate (CFRP) via ultrasound requires the knowledge of some important factors in addition to its structural composition. Since the laminates are heterogeneous, the high-frequency requirements to acquire high-resolution signals have limitations due to the great scattering that prevents good signal-to-noise ratios. Additionally, the ultrasonic probe’s spatial and lateral resolution characteristics are important parameters for determining the detectability level of microflaws. Modelling appears as a good approach to evaluating the abovementioned factors and the probability of detection of defects in the micron range because it makes it possible to reduce the time and cost associated with developments based on experimental tests. Concerning the subject of this work, simulation is the best way to evaluate the detectability level of the proposed defects since experimental samples are not available. In this work, the simulation was implemented using the Matlab k-Wave toolbox. A 2D matrix for mimicking a CFRP was constructed with 1 μm of resolution. Four different defect types in the micron range were created in the matrix. The simulated and experimental results presented good agreement. It was concluded that the highest frequency probe that could be used to detect the simulated defects without ambiguity was 25 MHz.